Derivatives: 16 x+35 2 (X+ H) 16 (X +H) +35 (2 X 16 x+35)
Derivatives: 16 x+35 2 (X+ H) 16 (X +H) +35 (2 X 16 x+35)
Derivatives: 16 x+35 2 (X+ H) 16 (X +H) +35 (2 X 16 x+35)
Examples:
1. f ( x )=2 x 2−16 x+ 35
( 2(x+ h)2−16( x +h)+35 ) −(2 x 2−16 x+ 35)
f ( x )=lim
h →0 h
( 2 ( x 2 +2 xh+ h2 )−16 x−16 h+ 35 ) −2 x 2 +16 x−35 ( 2 x 2+ 4 xh+2 h2 −16 x −16 h+35 ) −2 x 2 +16 x−35
¿ lim =lim
h→0 h h→ 0 h
( 4 xh+2 h2−16 h )
¿ lim
h→0 h
h ( 4 x+2 h−16 )
¿ lim
h→0 h
¿ lim 4 x +2 h−16
h→0
¿ 4 x−16
x
2. what is the derivative of f ( x )=
x +1
x+ h x
−
x +h+1 x+1
f ' ( x )=lim
h →0 h
h
(x+ h+1)( x +1)
f ' ( x )=lim
h →0 h
h
∗1
'( x ) ( x +h+1 ) ( x+ 1 )
f =lim
h→0 h
1
f ' ( x )=lim
h →0 (x +h+1)(x+1)
1
f ' ( x )=
( x+1 )2
5 x+ 5 h−8−5 x+ 8
f ' ( x )=lim
h→0 h( √ 5 ( x+ h )−8+ √5 x−8)
5h
f ' ( x )=lim
h→0 h( √ 5 ( x+ h )−8+ √5 x−8)
5
f ' ( x )=lim
h → 0 ( √ 5 ( x+ h )−8+ √ 5 x−8)
5
f ' ( x )=
( √ 5 x−8+ √ 5 x−8)
5
f ' ( x )=
2 √ 5 x−8
Properties of Derivatives
1. f ( x )=3=3 x 0
y ' =f ' ( x ) =0
3−3
f ' (x )=lim =¿ lim 0=0¿
h →0 h h→ 0
2. f ( x )=3 x
f ' (x )=3( x1−1 )
f ' (x )=3
3 (x+ h)−3 x
f ' (x )=lim
h →0 h
3 x +3 h−3 x
f ' (x )=lim
h →0 h
3h
f ' (x )=lim
h →0 h
f ' (x )=lim 3
h →0
f ' (x )=3
4. f ( x )=2 x 6 +7 x−4
f ' ( x )=2(6)x 6−1 +7(−4) x−4−1
f ' ( x )=12 x 5−28 x−5
28
f ' (x )=12 x 5− 5
x
3 1
5. f ( x )=8 x − 3 x 6 + x−23
1
f ( x )=8 x 3− ∗x −6 + x−23
3
1
f ' ( x )=24 x2 − (−6)∗x−6−1+ 1
3
'(x ) 2
f =24 x +2 x−7 +1
2
f ' (x )=24 x 2 + +1
x7
3 23
6. y= √ x−9 √ x 2+ 4 3
√x
1 2
23
y=x 2 −9( x 3 )+ 3
4
x
1 2 −3
2 3 4
y=x −9( x )+23 x
1 2 −3
' 1 −1 2 −1 −3 −1
y = x 2 −9( )( x 3 )+23( )x 4
2 3 4
−1 −1 −7
' 1
y = x 2 −6 x
2
( )− 694 x
3 4
1 6 69
y'= 1
− 1
− 7
2 3
2(x ) x 4 ( x 4)
1 6 69
y'= −3 − 4+3
2 √x √x 4
4(x )
1 6 69
y'= −3 − 4 3
2 √x √x +
4(x4 4 )
1 6 69
y'= −3 − 4 3
2 √x √x 4 4
4(x x )
1 6 69
y'= −3 − 3
2 √x √x 1
4(x x4 )
1 6 69
y'= −3 −
2 √ x √ x 4 x √4 x 3
7. y=x π−x √ 2
y ' =π x π−1− √2 x √ 2−1
8. y= √3 x 2 (2 x−x2 )
2
y=x (2 x−x 2)
3
2 2
y=x ( 2 x )−x ( x 2)
3 3
2 2
y=x ( 2 x )−x ( x 2)
3 3
5 8
3 3
y=2 x −x
5 5 −1 8 8 −1
y '=2( ) x 3 − x 3
3 3
10 23 8 53
y '= x − x
3 3
10 3 2 8 33 + 23
y '=
3
√x − 3 x
10 3 2 8 23
y '=
3
√ x − 3 xx
10 3 2 8 3 2
y '=
3
√x − 3 x √x
5
2x + x 2−5
9. f ( x )=
x2
2 x5 + x 2−5
f ( x )=
x2
2 x5 x 2 5
f ( x )= + −
x 2 x 2 x2
10
f ' (x )=6 x 2 +
x3
1+ x 1 x
= +
2 2 2
x2
3
2√ x5
10. f ( x )=
3
x
2
x
3
∗x
2√ x5
f ( x )=
3
x2
3
∗x
2√ x3 x2
f ( x )=
3
2
x
3
∗x
2 x √ x2
f ( x )=
3
2
x
3
∗1
2√ x2
f ( x )=
3
2
x
f ( x )= 2
6 x3
2
1 2− 3
f ( x )= ∗x
6
4
1
f ( x )= ∗x 3
6
4
1 4 −1
f ' ( x )= ( )∗x 3
6 3
1
2 2
f ' ( x )= x 3 = √3 x
9 9
Type equation here .
1
x3
3
11. 2 x5
f ( x )= 4√
√x
x
1
∗1
x3
3
2 x5
f ( x )= 4√
√x
x
1
∗1
x3
3
2 x3 x2
f ( x )= √4
√x
x
1
∗1
x3
3
2 x √ x2
f ( x )= 4
√x
x
1
4 3
2 x ( √ x 2)
f ( x )=
√4 x
x
1
4 3
∗x
2 x ( √ x 2)
f ( x )=
√4 x
1
2
∗1
3 3
2 x (x )
f ( x )= 1
x4
1
f ( x )= 2 1
(3+ + )
3 4
2x
1
f ( x )= 47
12
2x
−47
1 12
f ( x )= x
2
1 −47 −47 −1
f ' ( x )= ( ) x 12
2 12
−47 −59
f ' ( x )= x 12
24
−47
f ' ( x )= 12 12 12 12 11
( + + + + )
12 12 12 12 12
24 x
−47
f ' ( x )= 11
1 1 1 1 12
24 x x x x x
−47
f ' (x )= 12
24 x 4 √ x 11
Some of the Rules in Differentiation:
1. Product Rule
y=f ( x ) g ( x )
1. f ( x )= √ x (2 x −x )
3 2 2
2
f ( x )=x 3 (2 x−x 2)
2 −1
2
f ' ( x )=x 3 ( 2−2 x )+(2 x−x 2)( x 3 )
3
2 2 −1
2
f ' ( x )=2 x 3 −2 x x 3 +(2 x−x 2)( x 3 )
3
2 2
2 2
−1 −1
2
f ' ( x )=2 x 3 −2 x x 3 +2 ()
3
xx 3 − x x
3
3
2 5 2
4 2 5
f ' ( x )=2 x 3 −2 x 3 + x 3 − x 3
3 3
2 2 5
4 2 5
f ' ( x )=2 x 3 + x 3 −2 x 3 − x 3
3 3
10 5
'(x ) 8
f =2 x − x 3
3
3
1 2
3+ 8 1+
f ' ( x )=2 x 3
− x 3
3
8 3
f ' ( x )=2 x 3 √3 x− x √ x2
3
2. y=(6 x −x)(10−20 x)
3
'
y ' =( 6 x 3−x ) ( 10−20 x ) +(10−20 x)(6 x 3−x) '
Quotient rule:
f (x)
GIVEN : y =
g( x )
6−3 x+3 x +9
y '=
4−4 x+ x 2
15
y '=
4−4 x + x 2
4 X
2. y= x √−22
1
4 x2
y= 2
x −2
1 ' 1
( x −2 ) ( 4 x ) −4 x 2 ( x2 −2)'
2 2
y '= 2
( x 2−2 )
−1 1
( x 2−2 ) (2 x 2 )−4 x 2 (2 x)
y '= 2
( x2 −2 )
3 −1 3
2 2 2
2 x −4 x −8 x
y '= 4 2
x −4 x + 4
3 1
4
2 x 2 − 1 −8 x x 2
x2
y '=
x 4 −4 x2 + 4
4
2 x √ x− −8 x √ x
y '= √x
4 2
x −4 x +4
4
3. y= x 5
0−4 (5 x 4 )
y '=
( x ¿¿ 5)2 ¿
−20 x 4
y '=
x5 x 5
−20
y '=
x6
x4
4. y=
2
y '=2 x 3
sinx
3. y= cosx =sec x 2
sinx
y=
cosx
cosxcosx−sinx (−sinx)
y'=
co s2 x
1
y'=
co s2 x
y ' =sec 2 x
2 12 1
sin x= 2
= 2
csc x csc x
1
tanx=
cotx
1
sec 2 x=
cos 2 x
3. y=5 sinxcosx+ 4 cscx
y '=5 [sinx ( cosx )' +cosx ( sinx )' ]+ 4 (−cscxcotx )
sinx
4. y= 3−cosx
( 3−cosx ) sin x ' −sinx(3−cosx)'
y '=
( 3−cosx )2
( 3−cosx ) cosx−sinx(sinx)
y '=
( 3−cosx )2
3 cosx −1
y '=
9−2 cosx +cos 2 x
( 2 x−1)( secx)
5. y= sinx
(2 x−1)(secx)
5. y=
sinx
'
sinx [ ( 2 x−1 ) ( secx ) ] −(2 x−1)( secx)(sinx)'
y=
sin2 x
sinx[ ( 2 x−1 )( secxtanx ) +2 secx ]−(2 x−1)(secx)( cosx)
y= 2
sin x
sinx[ ( 2 x−1 )( secxtanx ) +2 secx ]−(2 x−1) secxcosx
y=
sin2 x
sinx[2 x secxtanx−secxtanx+ 2 secx]−(2 x−1)secxcosx
y=
sin 2 x
[2 xsecxtanxsinx−secxtanxsinx+ 2 secxsinx ]−(2 xsecxcosx−secxcosx)
y=
sin 2 x
2 xsecxtanxsinx−secxtanxsinx+2 secxsinx −2 xsecxcosx +secxcosx
y=
sin 2 x
1 1 1
2x tanxsinx− tanxsinx+2( ) sinx−2 x +1
cosx cosx cosx
y=
sin 2 x
sinx sinx sinx
2x tanx− tanx+2( )−2 x +1
cosx cosx cosx
y=
sin 2 x
2 x tanx tanx−tanxtanx+ 2tanx −2 x +1
y=
sin 2 x
2 xtan2 x−tan 2 x +2 tanx−2 x+1
y=
sin2 x
x2
6. y=
3 xsinx
Trigonometric Identities:
Tanx = sinx/cosx
Cotx = cosx/ sinx
2 5
1+ =
3 3
−1 4−1 3
2+( )= =
2 2 2
−47 −47 12 −47−12 −59
−1= − = =
12 12 12 12 12
2 11 1 44 +3 47
3+ = + = =
3 3 4 12 12
4
4 √ x4 x3
4
4 x √ x3
X*x = x^2 = x^1+1
1 2 3−4 −1 1 2 −1
− = = − =
2 3 6 6 4 4 4
1 2 3−2 1
− = =
2 6 6 6
2 2
∗4
3 3 4
¿ = =
2 2 3
4
2 2
∗1
3 3 1
¿ = =
2 2 3
1